2004
DOI: 10.1161/01.atv.0000145574.90840.7d
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species

Abstract: Abstract-Platelets participate not only in thrombus formation but also in the regulation of vessel tone, the development of atherosclerosis, angiogenesis, and in neointima formation after vessel wall injury. It is not surprising, therefore, that the platelet activation cascade (including receptor-mediated tethering to the endothelium, rolling, firm adhesion, aggregation, and thrombus formation) is tightly regulated. In addition to already well-defined platelet regulatory factors, such as nitric oxide (NO), pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
128
0
9

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 405 publications
(141 citation statements)
references
References 133 publications
4
128
0
9
Order By: Relevance
“…Platelets are exposed to ROS generated by the endothelial cells of the vessel walls; in addition, there is evidence that platelets can themselves produce ROS. Lastly, under inflammatory conditions, platelets are exposed the phagocyte-dependent, acute production of ROS [164].…”
Section: Plateletsmentioning
confidence: 99%
“…Platelets are exposed to ROS generated by the endothelial cells of the vessel walls; in addition, there is evidence that platelets can themselves produce ROS. Lastly, under inflammatory conditions, platelets are exposed the phagocyte-dependent, acute production of ROS [164].…”
Section: Plateletsmentioning
confidence: 99%
“…This may be either a direct effect of oxidant stress on the platelet [13] or an indirect effect through destruction of labile endothelium-derived vasodilators such as nitric oxide [14]. However, the direct effects of reactive oxygen species (ROS) on platelets are inconsistent with previous studies reporting both pro-and anti-aggregatory effects when platelets are exposed to exogenous ROS [15]. Oxidant stress generated either by platelets themselves via several intracellular sources [16] or by the artery wall can also modulate vascular tone [17] and this has implications for blood flow and thrombus formation within blood vessels.…”
Section: Introductionmentioning
confidence: 98%
“…The balance between oxidative stress and platelet production of NO plays a key role in the process of platelet recruitment, which is an important phase of platelet activation at the site of vascular injury (Freedman et al, 1997). It is recently reported that reactive oxygen species (ROS) influence platelet function and coagulation, and are associated with the pathogenesis of cardiovascular disease (Krotz et al, 2004;Gorlach, 2005;Arthur et al, 2008). In addition, polyphenols exert an antioxidant effect via inhibition of O2 − (superoxide) generation and suggest that this effect could result in enhanced NO bioavailability and inhibit platelet recruitment (Pignatelli et al, 2006).…”
Section: Discussionmentioning
confidence: 99%